Analysis of a gas-liquid-liquid-solid catalytic reaction: kinetics and modeling of a semibatch slurry reactor - Roy, D.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
Hydrogenation of aniline to cyclohexylamine was studied in a gas-liquid-liquid-solid tetraphase system using cyclohexane and water as two immiscible liquid phases and ruthenium on alumina (2% Ru/Al2O3) as the catalyst. In addition to the higher catalytic activity with respect to the conventional three-phase system, the novel four-phase system was highly efficient in catalyst-product separation. Experimental data on concentration-time as well as hydrogen-consumption-time profiles were obtained to study the effect of concentration of aniline, catalyst loading, and the partial pressure of hydrogen. A detailed analysis of gas-liquid, liquid-liquid, liquid-solid, and intraparticle mass transfer was carried out using initial rate data to ensure the kinetic regime. On the basis of these data, several rate equations were evaluated to select a kinetic model. The kinetic parameters were estimated over a temperature range of 378-418 K by fitting the integral batch reactor data. A rate model considering adsorption of hydrogen on the catalyst surface followed by reaction with the liquid-phase components as the rate-limiting step was found to give the best fitting of the experimental concentration-time as well as the hydrogen-consumption-time data at different initial sets of reaction conditions. The activation energies, heat of adsorption, and entropy of adsorption were also evaluated.

Carbonylation of alkynes, alkenes and alcohols using metal complex catalysts - Sarkar, B. R.; Chaudhari, Raghunath V. (Catalysis Surveys from Asia, 2005)
Carbonylation of olefins, alcohols and halides using homogeneous as well as heterogeneous catalysts has been discussed. Highlights of contributions on the activity, selectivity and stability of catalysts for carbonylation reactions are discussed. Kinetics and mechanism including characterization of the intermediate catalytic species has also been reviewed. The performance of anchored Pd complexes on mesoporous supports (MCM-41 and MCM-48), water soluble Pd complexes and supported Pd catalysts in carbonylation of aryl alcohols and olefins has been discussed in the context of catalyst-product separation. Some aspects of kinetic modelling and reaction engineering of these multiphase catalytic reactions have also been reviewed.
Keywords: Carbonylation; catalysis; Heterogenization; homogeneous; Palladium

Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

Dynamics of drop impact on solid surface: experiments and VOF simulations - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
The process of spreading/recoiling of a liquid drop after collision with a flat solid surface was experimentally, and computationally studied to identify the key issues in spreading of a liquid drop oil a solid surface. The long-term objective of this study is to gain an insight in the phenomenon of wetting of solid particles in the trickle-bed reactors. Interaction of a falling liquid drop with a solid surface (impact, spreading, recoiling, and bouncing) was studied using a high-speed digital camera. Experimental data oil dynamics of a drop impact on flat surfaces (glass and Teflon) are reported over a range of Reynolds numbers (550-2500) and Weber numbers (2-20). A computational fluid dynamics (CFD) model, based on the volume of fluid (VOF) approach, was used to simulate drop dynamics on the flat sufaces. The experimental results were compared with the CFD simulations. Simulations showed reasonably good agreement with the experimental data. A VOF-based computational model was able to capture key features of the interaction of a liquid drop with solid surfaces. The CFD simulations provide information about finer details of drop interaction with the solid surface. Information about gas-liquid and liquid-solid drag obtained from VOF simulations would be useful for CFD modeling of trickle-bed reactors. (C) 2004 American Institute of Chemical Engineers.
Keywords: CFD; drop impact; recoiling; spreading; trickle bed; VOF

Hydrodynamics of trickle-bed reactors: experiments and CFD modeling - Gunjal, P. R.; Kashid, M. N.; Ranade, V. V.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
{Hydrodynamics of trickle-bed reactors involve complex interactions of gas and liquid phases with packed solids. Such complex interactions manifest in different flow regimes occurring in trickle-bed reactors. Knowledge of prevailing flow regime, pressure drop, and liquid holdup is essential for design and performance evaluation of the reactor. Detailed knowledge of fluid dynamics is essential for ``a priory'' predictions as well as for interpretation of available data. In this study, we have used wall pressure fluctuation measurements to identify prevailing flow regime in trickle beds. Experiments were carried out on two scales of columns (of diameter 10 cm and 20 cm) with two sets of particles (3 min and 6 mm diameter spherical particles). Effects of prewetted and unwetted bed conditions on pressure drop and liquid holdup were reported for a range of operating conditions (V-G = 0.22-0.44 kg/m(2)s

Hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin: kinetic studies - Diwakar, Makarand M.; Deshpande, R. M.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2005)
The exchange of the Rh/Triphenylphosphine trisulfonate sodium [TPPTS] complex on to an anion exchange resin results in a stable heterogenized catalyst for the hydroformylation of alkenes. The kinetics of hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin to Amberlite IRA-93 has been investigated for the first time. The rate of the reaction was found to be dependent on the partial pressure of hydrogen and 1-hexene concentrations with a first order. A maximum in the rate with increasing partial pressure of carbon monoxide was observed. A rate model has been proposed which predicts the observed rate data within reasonable error. The activation energy was found to be 84.37 kJ/mol. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogenized catalyst; Hydroformylation; ion-exchange resin; kinetics; Rhodium

Isolation and characterization of an iodide bridged dimeric palladium complex in carbonylation of methanol - Tonde, S. S.; Kelkar, Ashutosh A.; Bhadbhade, Mohan M.; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2005)
Palladium-catalyzed carbonylation of methanol in presence of iodide promoters was investigated. Iodide bridged palladium dimeric complex, [PPh3CH3](2)[Pd2I6] was isolated from the carbonylation reaction mixture and characterized using X-ray crystallography. Reaction mechanism was proposed based on IR and UV spectroscopic characterizations of catalytic species involved in the catalytic cycle. The isolated dimeric palladium species, [Pd2I6](2-) underwent carbonylation to give monomeric species [PdI3CO](-) at atmospheric pressure of carbon monoxide. It was also observed that PPh3 plays an important role to avoid catalyst deactivation at higher temperatures. Turnover frequency (TOF) of 1052 h(-1) was achieved using Pd(OAC)(2)-HI-PPh3 catalyst system at 175 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dirneric palladium; IR spectroscopy; methanol carbonylation; palladium catalyst; reaction mechanism; UV

Kinetic modeling of reductive alkylation of aniline with acetone using Pd/Al2O3 catalyst in a batch slurry reactor - Roy, D.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
The kinetics of reductive alkylation of aniline with acetone was studied in a slurry reactor under isothermal conditions in a temperature range of 378-408 K using 3% Pd/Al2O3 catalyst. Experimental data on concentration-time as well as hydrogen consumption-time profiles were obtained to study the effect of concentration of aniline, catalyst loading, and partial pressure of hydrogen. Separate controlled experiments were performed to understand the nature of the condensation reaction between aniline and acetone, which forms the Shiff's base intermediate. From the concentration-time profiles and the effect of reaction conditions, it was found that the noncatalytic equilibrium formation of the Shiff base intermediate was the slowest step in the multistep reaction sequence. Several rate equations were considered to fit the batch slurry reactor data, and rate models based on competitive dissociative adsorption of hydrogen and the reactive substrates in the rate-limiting catalytic steps were found to represent the experimental data. The kinetic parameters were evaluated by fitting the integral batch reactor data at different temperatures. The activation energies, heat of adsorption, and entropy of adsorption of all the reactant species were also evaluated.

New route for the synthesis of propylene glycols via hydroformylation of vinyl acetate - Borole, Yogesh L.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
Hydroformylation of vinyl acetate (VAM) has been studied as a key step in the alternative route for the synthesis of 1,2-propanediol (1,2-PDO) and 1,3-propanedol (1,3-PDO) using homogeneous rhodium (Rh) and cobalt (Co) complex catalysts. The feasibility of the VAM hydroformylation route has been demonstrated, and a detailed study has been reported on the key hydroformylation step using homogeneous Rh and Co catalysts. The roles of the catalyst precursors, ligands, and solvents in the activity and regioselectivity of the aldehyde products, i.e., 2-acetoxy propanal (2-ACPAL) and 3-acetoxy propanal (3-ACPAL), and the effect of reaction conditions have been investigated. With Rh-phosphine catalysts, 2-ACPAL is obtained with a selectivity of > 90%, while with cobalt carbonyl catalyst, 2-ACPAL and 3-ACPAL are formed with comparable selectivities (similar to 50% each) thus substantially improving the selectivity of the linear aldehyde, a precursor for 1,3-PDO. In halogenated solvents with cobalt carbonyl catalyst, the selectivity to 3-ACPAL was found to increase still further (58%). A possible mechanism to explain the variation in regioselectivity for the Rh anal Co catalysts has been discussed. In the presence of pyridine as a ligand in the Co-catalyzed hydroformylation of VAM, the rate of reaction was found to be enhanced 4-fold. The hydrogenation of acetoxypropanal isomers using Raney-Ni catalyst followed by hydrolysis using Amberlite IR-120 resin catalyst gave quantitative conversion to the mixture of 1,2- and 1,3-PDOs (> 90% yield).

Selective synthesis of N,N-dimethyl aniline derivatives using dimethyl carbonate as a methylating agent and onium salt as a catalyst - Shivarkar, A. B.; Gupte, S. P.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A - Chemical, 2005)
N-Alkylation of anilines by dimethyl carbonate (DMC) catalyzed by onium salts has been demonstrated. The work presented here shows that a simple catalytic system consisting of onium salts in the presence of a small amount of water is extremely effective in enhancing the DMC mediated N-alkylation of anilines to dialkylated products. The effect of reaction conditions on the synthesis of N,N-dimethyl aniline (NNDMA) from aniline and DMC has been investigated. Under the optimized conditions highest yield of NNDMA obtained was 99.8%, which is the best reported for liquid phase N-alkylation of aniline using DMC. The role of water in enhancing the yield of NNDMA is explained and a reaction-networking scheme is constructed, which summarizes the chemistry behind liquid phase N-alkylation of anilines by DMC. The catalyst has been shown to recycle up to five times and at the end of fifth recycle almost 98% of NNDMA yields were obtained. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Aniline; Dimethyl carbonate; methylation; N; N-alkylation; N-dimethyl aniline; onium salts

Hydroformylation of olefins using dispersed molecular catalysts on solid supports - Pagar, N. S.; Deshpande, R. M.; Chaudhari, Raghunath V. (Catalysis Letters, 2006)
A new method for heterogenization of metal complex catalysts by precipitation of its water-soluble analogue as a Gr.2 metals (Ca, Sr or Ba) salt on porous supports has been proposed. This technique yields a highly dispersed catalyst having a significantly higher activity (TOF) for hydroformylation of olefins compared to other known heterogenized catalysts. The catalyst can be recycled with ease.
Keywords: carbon support; Heterogenization; Hydroformylation; Olefins; Rhodium

Ossification: a new approach to immobilize metal complex catalysts - applications to carbonylation and Suzuki coupling reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Journal of Catalysis, 2006)
A simple approach for immobilization of transition metal complexes is reported here based on the transformation of the complex into its intrinsically insoluble counterpart, thus generating solid molecular catalysts. This approach that we call ``ossification'' is based on a principle, in which the water-soluble analogues of the metal complexes are precipitated out from aqueous solutions as insoluble ionic ensembles having catalytically active metal-centered coordination environments and robust framework. The approach has been illustrated for I'd complex catalyzed carbonylation and Suzuki coupling reactions. ``Ossification'' was found to be an economically and environmentally attractive alternative to other exotic immobilization methodologies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Carbonylation; Heterogeneous catalysts; Immobilization; ossification; Palladium complex; Suzuki coupling

Synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates using Na-Y zeolite catalyst - Shivarkar, Anandkumar B.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synlett, 2006)
A simple, efficient, and environmentally benign methodology for the synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates in the presence of the highly active and reusable solid base catalyst Na-Y zeolite is demonstrated.
Keywords: Alkylation; alkylene carbonate; Amine; Amino alcohols; zeolite

Bimetallic Pt-Sn/gamma-alumina catalyst for highly selective liquid phase hydrogenation of diethyl succinate to gamma-butyrolactone - Vaidya, S. H.; Rode, C. V.; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Platinum-tin bimetallic catalyst on gamma-alumina support was prepared by impregnation method and was reduced by sodium borohydride at room temperature. XRD and XPS characterization revealed that platinum was reduced to Pt-0 while, tin was probably partially reduced to Sn2+ due to the low temperature reduction method and Sn-0 was completely absent, avoiding the formation of P-Sn alloy. Pt-Sn/gamma-alumina (Pt 1%, Sn 9%) thus prepared was found to give almost complete selectivity to gamma-butyrolactone in liquid phase hydrogenation of diethyl succinate. A plausible reaction pathway is proposed involving Pt-O-Sn state and high selectivity to GBL is due to the Lewis acidity of Sn2+/4+ (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bimetallic Pt-Sn catalyst; gamma-butyrolactone selectivity; liquid phase hydrogenation of diethyl maleate; XPS of Pt-Sn; XRD of Pt-Sn

Biphasic hydroformylation of 1,4-diacetoxy-2-butene: a kinetic study - Chansarkar, Rashmi; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 1,4-diacetoxy-2-butene was studied using a water-soluble Rh complex catalyst prepared in situ from [Rh(COD)Cl](2) complex and trisodium salt of tri-(m-sulfophenyl)phosphine (TPPTS) in a biphasic system. The sequence of addition of catalyst precursor, ligand, and reactant/solvent showed a significant effect on leaching of Rh from aqueous to organic phase, and hence, the procedure was optimized to develop a nonleaching and stable biphasic catalyst system. The only hydroformylation product (1,4-diacetoxy-2-formyl butane, DAFB) formed was found to deacetoxylate completely to 2-formyl-4-acetoxybutene (FAB), thus allowing a one-pot synthesis of FAB, an important intermediate for Vitamin A. Experimental data on the concentration-time and CO/H-2 consumption-time profiles were obtained, and the effects of DAB concentration, CO partial pressure, H-2 partial pressure, and catalyst concentration were studied in a stirred batch reactor over a temperature range of 338-358 K. The effect of aqueous phase holdup on the initial rate of hydroformylation and analysis of gas-liquid and liquid-liquid mass transfer effects were also investigated to identify the reaction rate data operating in a kinetic regime. A rate equation based on the known hydroformylation reaction mechanism was used to fit the experimental rate data and to evaluate kinetic parameters. The agreement between the model prediction and the experimental data was found to be excellent. The activation energy was calculated as 30.1 kJ/mol. The biphasic catalyst system reported here is not only efficient for catalyst-product separation but also provides a tandem synthesis of Vitamin A intermediate, FAB.

Environmentally benign catalytic hydroformylation-oxidation route for naproxen synthesis - Rajurkar, Kalpendra B.; Tonde, Sunil S.; Didgikar, Mahesh R.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 6-methoxy-2-vinylnaphthalene (MVN), using homogeneous Rh(CO)acac) as a catalyst and a chelating bidentate ligand (1,2-bis-(diphenylphosphino) ethane, dppe), followed by oxidation of the product (2-(6-methoxynaphthyl) propanal, 2-MNP) has been studied as an alternative route for the synthesis Of D,L-naproxen. The feasibility of the MVN hydroformylation route has been demonstrated, and a detailed study has been reported on the key hydroformylation step. The roles of the catalyst, ligands, and solvents, as well as the effect of reaction conditions on the reaction rate and regioselectivity of the product 2-MNP, have been investigated. With Rh(CO)2(acac) as a catalyst and dppe as a ligand, > 98% selectivity to 2-MNP (an important precursor to D,L-naproxen) has been achieved. A possible mechanism to explain the variation in regioselectivity with Rh(CO)(2)(acac) as a catalyst and dppe as a ligand has been discussed. The kinetics of the hydroformylation step has been investigated and a rate equation has been proposed. The second step in the proposed route for naproxen-the oxidation of 2-MNP to 2-(6-methoxynaphthyl) propanoic acid (2-MNPA, or naproxen) - has been studied using Na2WO4 as a catalyst and tetrabutyl ammonium hydrogen sulfate (TBAHS) as the phase-transfer catalyst with H2O2 as the oxidant for the first time. Screening of the catalysts that consisted of the early transition metals, such as salts of tungsten, vanadium, and molybdenum showed that Na2WO4 gives the best performance for the oxidation step with > 80% selectivity to 2-(6-methoxynaphthyl)propanoic acid (2-MNPA/naproxen). This study would be valuable in developing a new environmentally benign route for naproxen synthesis.

Kinetics of reductive alkylation of p-phenylenediamine with methyl ethyl ketone using 3% Pt/Al2O3 catalyst in a slurry reactor - Patil, Narendra G.; Roy, Debdut; Chaudhari, Amit S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Intrinsic kinetics of reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) using 3% Pt/Al2O3 catalyst was studied in a slurry reactor. The overall reaction involves a combination of parallel and consecutive reactions involving equilibrium noncatalytic (homogeneous) and catalytic (heterogeneous) steps. For the purpose of kinetic modeling, the effects of PPDA concentration, catalyst loading, agitation speed, and partial pressure of hydrogen were studied in a temperature range of 373-413 K. Quantitative criteria were used to ensure that the reaction occurred in the kinetic regime. Different rate equations have been considered based on the elementary steps involving catalytic and noncatalytic reactions, which lay stress on the different types of interactions occurring between the reactants and the active catalyst sites. The best-fit rate model has been proposed by rigorous optimization and model discrimination procedures, by simulating the experimental concentration-time data. For the best-fit model, the agreement between the predicted and experimental data was found to be very good over a wide range of operating conditions.

Modeling of bubble column slurry reactor for reductive alkylation of p-phenylenediamine - Chaudhari, Amit S.; Rampure, Mohan R.; Ranade, Vivek V.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Chemical Engineering Science, 2007)
A bubble column slurry reactor (BCSR) model has been developed for the reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) to N, N'-di-secondary-alkyl-p-phenylenediamine (Di-amine). This particular reaction system is commercially relevant and involves a combination of parallel and consecutive reactions comprising equilibrium non-catalytic (homogeneous) and catalytic (heterogeneous) steps. The proposed model is based on the `mixing cell approach'. In this work the mixing cell approach has been extended by including a liquid backflow stream from all but the bottommost mixing cell. The model incorporates the contributions of gas-liquid and liquid-solid mass transfer, heat effects, and complex multistep reaction kinetics. CFD model is used to estimate the extent of backflow among mixing cells and its dependence on operating parameters. The effect of gas and liquid velocities, catalyst loading, inlet PPDA concentration, and temperature on the conversion, selectivity, global rate of hydrogenation, and temperature rise is discussed. The comparison of the current approach with the traditional mixing cell model is discussed. The BCSR model presented here will be useful to provide guidelines for designing and improving overall performance of bubble column reactors. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: bubble columns; CFD; kinetics; Mathematical modeling; Reductive alkylation

Preface: CAMURE-6 & ISMR-5 symposium in Pune, India - Chaudhari, Raghunath V.; Ranade, Vivek V. (Industrial & Engineering Chemical Research, 2007)

Rate enhancement in palladium catalyzed Heck reactions by Lewis acid promoters - Sud, Abhishek; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Significant enhancement in the rate of Heck reactions has been achieved when catalytic amounts of Lewis acid (like FeCl(3)) promoters in the presence of trace amounts of water (> 2000 ppm) are used along with Pd complex catalysts. Experiments with different aryl halides, bases as well as olefins have been carried out to demonstrate the role of Lewis acid promoters. The increase in the reaction rates is due to the weakening of Ar-X bond by the Lewis acid in the manner similar to Friedel-Crafts reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Heck reaction; Lewis acid; Palladium; Promoters

Tethered Pd-complex on solid support: catalyst for acid-free carbonylation reactions - Sarkar, Bibbas R.; Mukhopadhyay, Kausik; Chaudhari, Raghunath V. (Catalysis Communictions, 2007)
{Palladium complex [
Keywords: decomposition; direct H2O2 synthesis; halides; Promoter

Highly efficient sulfimidation of 1,3-dithianes by Cu(I) complexes - Giribabu, Lingamallu; Singh, Surya P.; Patil, Nandkumar M.; Kantam, M. Lakshmi; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synthetic Communications, 2008)
A series of four Cu(I) complexes were tested for sulfimidation of 1,3-dithianes in the presence of [N-(p-tolysulfonyl)imino]phenyliodinane (PhI = NTs) as the nitrene-transfer agent. Cu(TMPhen)(PPh3)Br is an efficient catalyst with more than 90% yield of the corresponding product with less reaction time as compared to the literature copper(I) complexes.
Keywords: 1; 3-dithianes; Cu(I) complexes; PhI = NTs; sulfimidation

Highly selective synthesis of mono-ethylene glycol phenyl ethers via hydroxyalkoxylation of phenols by cyclic carbonates using large pore zeolites - Kinage, Anil K.; Gupte, Sunil P.; Chaturvedi, Rajiv K.; Chaudhari, Raghunath V. (Catalysis Communications, 2008)
Hydroxyalkoxylation of phenols by cyclic carbonates catalyzed by alkali loaded large pore zeolites has been reported. The study shows that KL type zeolite was recyclable and selective in producing mono-ethylene glycol pheryl ethers in similar to 98.5% yield. Various substituted simple phenols were converted into mono-ethylene glycol ether of phenols with over 90% yields, except 3-bromo and 2-methyl phenols. Mono hydroxyl plienols such as hydroquinone, biphenol and BPA (2,2-bis(4-hydroxyphenyl)propane) also produce corresponding mono- and di-ethylene glycol ethers. The ratio of ethylene carbonate to phenol was found to be critical for selective formation of monoethylene glycol phenyl ether of phenols. A ratio of two results in formation of appreciable amount of diether derivative viz., 2-(2-phenoxyethoxy) ethanol. Compared to ethylene carbonate, a lower reactivity of 1,2-propane carbonate was found for hydroxyalkoxylation of phenol. It was found that ring opening at less hindered methylene carbon of 1,2-propylene carbonate prevailed giving rise to selective formation of beta-hydroxy phenyl ethers. The reactivity of ethylene carbonate towards O-alkylation versus transesterification of phenol has been explained on the basis of HSAB concept. Finally, it has been shown that yield of mono-ethylene glycol phenyl ether is controlled both by basicity and channel architecture of zeolite structure. KL zeolite was found to be the most effective zeolite because of it's intermediate basicity and one dimensional channel architect. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cyclic carbonate; ethylene glycol phenyl ether; hydroxyalkoxylation; phenol

Tandem synthesis of beta-amino alcohols from aniline, dialkyl carbonate, and ethylene glycol - Shivarkar, Anandkumar B.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2008)
An efficient tandem route for selective synthesis of beta-amino alcohols from anilines, dialkyl carbonate and ethylene glycol in the presence of recyclable Na-Y zeolite has been demonstrated. Transesterification of dialkyl carbonate by ethylene glycol produce ethylene carbonate which further reacts with aniline to give beta-amino alcohols in a single step. This reaction system was studied under high-pressure as well as pot reaction condition. Various process parametric effects were investigated for the reaction of aniline, dialkyl carbonate, and ethylene glycol. It was observed that a maximum 51% yield of mono-beta-amino alcohol, i.e., N-phenylethanolamine (NPEA). is obtained under pressure conditions. The yield of NPEA was improved drastically (>91%) by carrying out the reaction under pot conditions using diethyl carbonate as transesterification agent. Finally activity and selectivity of solid catalyst was explained on the basis of nature of active sites and pore structure of the catalyst.

Ultrasound promoted asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system - Shingote, Savita K.; Kelkar, Ashutosh A.; Borole, Yogesh L.; Joshi, Pradip D.; Chaudhari, Raghunath V. (Ultrasonics Sonochemistry, 2008)
Asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system proceeds with significant rate enhancement by ultrasound promotion. Comparison of the silent reactions carried out at 25 degrees C with reactions under sonochemical activation at 25 degrees C clearly showed enhancement in catalytic activity by 5-10 times without significantly affecting the enantioselectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: asymmetric catalysis; transfer hydrogenation; Ultrasound

Hydroesterification of 2-vinyl-6-methoxynaphthalene using palladium complexes containing chelating nitrogen ligands - Atla, Shashi B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
Hydroesterification of 2-vinyl-6-methoxynaphthalene (VMN) to methyl ester of 6-methoxy naphthyl propionic acid (ester of naproxen) has been investigated using palladium complexes containing the chelating N(boolean AND)O and N(boolean AND)N ligands (pyridine-2-carboxylate, 2-acetylpyridine, 2-pyridine-carboxaldehyde, and bipyridine) as catalysts. Palladium complex containing 2-acetylpyridine as the ligand was found to be superior to other Pd-complexes. Both acid and halide promoters were necessary for high activity and selectivity. As an acid promoter, benzenesulfonic acid was found to be more effective compared to p-toluenesulfonic acid. Formation of ether 2-methoxy-6-(1-methoxyethyl)naphthalene and a polymer of VMN was observed in all the reactions. It was observed that active catalytic species generated during carbonylation reaction was responsible for the polymer formation. The effect of various parameters such as solvents, CO pressure, and alcohols on the catalytic activity as well as the selectivity was investigated. The turnover frequency using the complex Pd(acpy)(PPh(3))(OTs)(2) (acpy = 2-acetylpyridine) catalyst was found to be 42 h(-1), which is the highest for the hydroesterification of VMN. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Carbonylation; Hydroesterification; Naproxen; Palladium complex; Polymer of VMN; Promoters

Hydroformylation of 1,4-diacetoxy-2-butene using HRh(CO)(PPh3)(3) tethered on alumina as a catalyst: kinetic study - Chansarkar, Rashmi; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2009)
Hydroformylation of 1,4-diacetoxy-2-butene (DAB) was studied using [HRh(CO)(PPh3)(3)] complex catalyst tethered on alumina using phosphotungstic acid (PTA) as an anchoring agent, with the aim to understand the product distribution, selectivity, and intrinsic kinetics. It was observed that with the tethered heterogeneous catalyst a simultaneous hydroformylation followed by deacetoxylation steps was possible, which is relevant for combining two steps in the sequence of synthesis of vitamin-A intermediate [2-formyl-4-acetoxy butene (FAB)]. P-31 cross-polarization magic angle spinning nuclear magnetic resonance (CP MAS NMR) and infrared (IR) instrumental techniques were found be the most effective techniques to establish the catalyst structure and true heterogeneity. On the basis of the spectroscopic evidence, we postulate the loss of a PPh3 group during tethering to give HRh(CO)(PPh3)(2)-PTA-Al2O3 as a heterogeneous complex catalyst. Experimental data on the concentration-time and CO/H-2 consumption-time profiles were obtained and the effects of DAB concentration, CO partial pressure, H-2 partial pressure, and catalyst loading were studied in a 50 mL stirred batch reactor over a temperature range of 338-358 K. The analysis of solid-liquid-gas mass transfer effects was investigated to ensure that the reaction was operating in the kinetic regime Various models were developed, and the best model was chosen by a model discrimination procedure. The agreement between the model prediction and the experimental data was found to be excellent. The activation energies for the hydroformylation and deacetoxylation steps were found to be 42.5 and 80.2 kJ/mol.

Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle

NC palladacycles in the Heck arylation of ethylene: synthesis, structure and their reactivity - Atla, Shashi B.; Kelkar, Ashutosh A.; Puranik, Vedavati G.; Bensch, Wolfgang; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2009)
Monomeric cyclopalladated complexes with NC coordination using ligands 2-phenylpyridine, 2-phenylquinoline, 8-methylquinoline have been synthesized and the structures have been determined by single crystal X-ray structure analysis. The crystal structures of monomeric palladacycles prepared using benzophenone oxime, and 2-phenylpyridine have also been determined. The use of these complexes in the Heck arylation of ethylene with 2-bromo-6-methoxynaphthalne (BMN) to give 2-vinyl-6-methoxynapthalene which is an intermediate for the synthesis of anti-inflammatory drug Naproxen has been examined and also arylation of ethylene with 3-bromo-benzophenone and 4-bromo-isobutylbenzene was investigated. These palladacycles with NC coordination show excellent catalytic activity with a TOF > 4000 h (1). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aryl propionic acids; Arylation; Palladacycle

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

Heterogenized copper catalysts for the amination of arylhalide: synthesis, characterization and catalytic applications - Patil, Nandkumar M.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Applied Catalysis A-General, 2010)
This research investigated the synthesis, characterization and catalytic activity of heterogenized copper complexes for the selective amination of aryl halides. Amination reactions using homogeneous copper catalyst systems are not generally selective and it is also difficult to recover the catalyst from the homogeneous system for recycling. To overcome these difficulties, our efforts were directed towards the development of cheaper heterogeneous catalyst systems, which can be easily recovered and recycled. Heterogenized analogs of the homogenous Cu complexes were prepared using two methods: (a) encapsulation of copper complexes in zeolite-Y and (b) tethering of copper complexes on various supports like zeolite-Y, silica, charcoal, or clay. The encapsulated and tethered copper catalysts on zeolite-Y were characterized using EPR, Diffused reflectance UV-vis, XRD, IAS, ICPES, SEM, and TEM. The results confirmed that the copper complexes were truly heterogenized in zeolite-Y support. Encapsulated and tethered copper complexes were tested for amination of aryl iodide. The effects of various reaction parameters were examined using tethered Cu(Phen)(PPh(3))Br-PTA-Y catalyst to determine optimum conditions. A recycle study of encapsulated and tethered Cu catalyst was carried out to test their robustness for possible commercial exploitation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amination; C-N coupling; Copper; heterogeneous catalysis; mesoporous materials

Immobilized palladium nanoparticles catalyzed oxidative carbonylation of amines - Didgikar, Mahesh R.; Roy, Debdut; Gupte, Sunil P.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2010)
Catalytic application of immobilized palladium nanoparticles for synthesis or ureas by oxidative carbonylation of amines has been investigated. This is the first report oil oxidative carbonylation of amines to ureas using immobilized palladium nanoparticles catalyst. The palladium nanoparticles were immobilized on a NaY zeolite support through 3-aminopropyl-trimethoxysilane (APTS) as anchoring agent. The [Pd]-APTS-Y catalyst along with NaI promoter showed high conversion and selectivity to the desired urea products over several amine compounds including ail example of an aliphatic amine precursor even at 333 K. The immobilized catalyst was easily separated and recycled several times without any loss of activity. The role of different solvents, iodide promoters, iodide to Pd ratio, concentration of substrates, and temperature on the overall yield of the reaction was also investigated.

Kinetics of reductive alkylations of phenylenediamines: influence of substrates isomeric structure - Roy, Debdut; Chaudhari, Amit S.; Chaudhari, Raghunath V. (Chemical Engineering Science, 2010)
Reductive alkylation of ortho-, meta- and para-phenylenediamines (PDAs) with methyl ethyl ketone (MEK) has been studied in a semi-batch slurry reactor in the presence of a commercial 3% Pt/Al(2)O(3) catalyst. It was observed that the PDA isomers differ remarkably from each other in their activity in reductive alkylation and product distribution. The activity was found to decrease in the following order: PPDA > OPDA > MPDA. To understand the substrate structure-activity correlation, the homogeneous equilibrium reactions involved in the alkylation step and the overall catalytic reactions were studied separately. Kinetics of reductive alkylation of PDAs with MEK as a solvent and alkylating agent with 3% Pt/Al(2)O(3) catalyst was studied in a semi-batch slurry reactor over a temperature range of 373-453K and pressure range of 2.07-6.21 MPa. Semi-batch slurry reactor models were developed and kinetic parameters were estimated by fitting the integral batch reactor data at different temperatures to understand the influence of different reaction steps on the activity and selectivity of different products. Published by Elsevier Ltd.
Keywords: Batch; catalysis; kinetics; Multiphase reactions; Phenylenediamines; Reaction engineering; Reductive alkylation

Oxidative carbonylation of amine using water-soluble palladium catalysts in biphasic media - Didgikar, Mahesh R.; Joshi, Sunil S.; Gupte, Sunil P.; Diwakar, Makarand M.; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2011)
Application of water-soluble palladium catalysts for oxidative carbonylation of aniline to N,N' diphenyl urea (DPU) has been reported. The water-soluble palladium catalysts prepared from sulfonated N-containing ligands were found to be highly stable under reaction conditions and easily recyclable due to insoluble urea product in the reaction medium. This is in contrast to the sulfonated phosphine ligands, which are vulnerable to oxidation under reaction conditions, showing poor activity and stability. Commercially available as well as laboratory synthesized ligands were used for preparing water-soluble palladium catalysts, for oxidative carbonylation of aniline. The best activity was obtained for Pd complex with disodium 2,2'-bipyridine-4,4'-disulfonate (Bipy-DS) ligand. Under optimized conditions Pd(BipyDS)Pd(OAc)(2) catalyst gave TOF of similar to 210h(-1) with aniline conversion of similar to 97% with similar to 91% selectivity for N.N'-diphenyl urea. It was found that the catalyst was easily reusable up to five times, with negligible loss in the catalytic activity. The effect of reaction parameters was investigated and a plausible reaction mechanism has been proposed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amine; Biphasic catalysis; Carbonylation; Urea; Water-soluble palladium catalyst

Anchored Pd-complexes in mesoporous supports: synthesis, characterization and catalysis studies for carbonylation reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Catalysis Today, 2012)
Pd(pyca)(PPh3)(OTs) [pyca = 2-picolinate] complex is efficiently anchored inside different mesoporous matrices, such as MCM-41, MCM-48, SBA-15 using a molecular aminopropyl tether moiety employing different synthesis strategies. Thorough characterization of the materials using powder XRD, multinuclear (C-13, Si-29, P-31) CP-MAS NMR, XPS, SEM, N-2-sorption studies etc. confirmed the successful anchoring of the palladium complex to the walls of the support matrices thus establishing the synthesis protocols unambiguously. The catalysts were found to be highly active and selective for the carbonylation of different aryl olefins and alcohols. Consecutive recycling and successful reuse proved the stability and true heterogeneous nature of all the anchored catalysts, which is a substantial advancement over the existing heterogeneous catalysts for carbonylation. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Anchored catalysts; Carbonylation; Immobilization; mesoporous materials; Palladium complex

Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.